Modeling and thermal energy management in smart homes - Khlifi, Khaoula (2020)
In this paper, it is demonstrated the importance of the information concerning the power flow and the state of a building’s thermal system for the management and control of electricity consumption. The proposed approach is evaluated simulating the heating exchange behavior of a configurable base model for an isolated and non-thermally insulated habitat in order to determine the influence of the energy losses on the control system. Based on the results obtained with this study, some improvements were carried-out for the management system of the heating flow by introducing appropriated parameters into the control algorithm.